IFS science grants - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Building science capacity in developing countries has been the objective of the International Foundation for Science (IFS) for more than 20 years. To identify young scientists of merit who have the potential for becoming, the future research...